(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
This proposal aims to explore emerging topics about the relationship between the moving image and the arts of the body in the production of contemporary audiovisual. To this end, we intend to address the theme of time as a force/intensity that crosses and constitutes creation in the contemporary audiovisual context, investigating its possible effects on the tensions between cinema, body and scenic dance. Such an approach is located at a zone of confluence, where Eastern and Western artistic-philosophical concepts meet. In this sense, we propose the exhaustion of the cinematographic device in the processes of creation and circulation as a form of invitation to another poetic treatise of time. Thus, from the intersections of this field of forces and relations between cinema, body and time, we propose to question whether it would be possible to devise a butoh effect in the context of contemporary audiovisual.